The second round of livestock feed and forage technology media engagement - Mekonnen, Kindu; Gebreyes, Million; Bezabih, Melkamu; Adie, Aberra; Assefa, Getenet; Seifu, Haimanot; Mesfin, Hailemariam (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
During the first round of media engagement, media assessment was conducted in three regions (Amhara, Oromia and SNNPR), aiming to identify appropriate regional radio stations, paving the way for a possible partnership with the media houses and understanding capacity (training) needs for journalists. As a result, Debre Birhan Fana FM 94.0 / Debre Birhan, OBN FM 96.5 / Bale and, Hosaena FM 95.3 / Hossaena were identified as appropriate regional radio stations. Then a partnership agreement was signed between the regional media houses and ILRI / Africa RISING and AICCRA projects to produce and broadcast weekly radio programs on livestock feed and forage innovations. Because of the limited awareness and knowledge of journalists on livestock feed and forage innovations, a two days media training workshop on climate-smart feed and forage innovations was also organized in Addis Ababa. Then the media houses produced and broadcasted 29 weekly radio programs (20 minutes each) on livestock feed and forage innovations. Finally, a quick evaluation of the radio broadcast was done and below were among the findings: The attention given to the livestock sector is insignificant and no media is working on the livestock sector as a standalone program other than as a side issue. Therefore, every media leader should be aware of the sector’s benefits and recommend the media to work on the livestock sector which will ultimately benefit the country.